2019
DOI: 10.1007/s10661-019-7232-7
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of artificial floods for benthic community recovery after sediment flushing from a dam

Abstract: The number of dams is predicted to increase worldwide under the current global change scenario. A major environmental problem associated with dams is the release of large quantities of fine sediment downstream. Therefore, future studies in river conservation will largely be focused on the management of sediments trapped by reservoirs. The aim of this study was to investigate the downstream ecological impacts of sediment flushing from a dam and the effectiveness of artificial flash floods as a recovery strategy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 49 publications
0
30
0
5
Order By: Relevance
“…Flow cessation results in the loss of the longitudinal connectivity and isolation of stream reaches with consequences on population survival, the diversity of aquatic communities, and transport and storage of organic matter subsidies (Datry et al 2016b;Doretto et al 2020). Such adverse conditions may be exacerbated by the effect of anthropogenic-induced hydromorphological alterations at the local scale, such as damming and water abstraction (Grubbs and Taylor 2004;Holt et al 2015;Doretto et al 2019;Piano et al 2019). Regardless of the nature of these alterations (i.e., natural or human-induced), RCC poorly adapts to lotic ecosystems experiencing changes in flow regime, with deviations from its predictions probably depending on the components of the flow regime that are mostly modified (i.e., magnitude, frequency, duration, timing, and flashiness).…”
Section: The Role Of Natural Discontinuitiesmentioning
confidence: 99%
“…Flow cessation results in the loss of the longitudinal connectivity and isolation of stream reaches with consequences on population survival, the diversity of aquatic communities, and transport and storage of organic matter subsidies (Datry et al 2016b;Doretto et al 2020). Such adverse conditions may be exacerbated by the effect of anthropogenic-induced hydromorphological alterations at the local scale, such as damming and water abstraction (Grubbs and Taylor 2004;Holt et al 2015;Doretto et al 2019;Piano et al 2019). Regardless of the nature of these alterations (i.e., natural or human-induced), RCC poorly adapts to lotic ecosystems experiencing changes in flow regime, with deviations from its predictions probably depending on the components of the flow regime that are mostly modified (i.e., magnitude, frequency, duration, timing, and flashiness).…”
Section: The Role Of Natural Discontinuitiesmentioning
confidence: 99%
“…species or taxa) that live in a certain habitat (Colwell 2009), is a key definition in community ecology with direct applications for basic and applied research. Measures and indices of biodiversity are generally used to get insights on the variation of biological communities along environmental gradients (Bo et al 2016;Falasco et al 2018) and in response to anthropogenic pressures (Bona et al 2016;Doretto et al 2018Doretto et al , 2019.…”
Section: Introductionmentioning
confidence: 99%
“…In that case, the long recovery time was mainly associated to ash accumulation and remobilization from hillslopes, and was comparable to that observed after ashfall (Anderson, 1992;Dorava & Milner, 1999) or landslide (Cover et al, 2010;Danehy et al, 2012;Lamberti et al, 1991) episodes (i.e., in the order of years). Recovery times of about 2 years were also reported after small dam removal (Carlson et al, 2018;Tullos, Finn, & Walter, 2014) and after an uncontrolled sediment release (Doretto et al, 2019). Shorter recovery times of benthic communities were generally documented in regulated Alpine streams subjected to controlled sediment flushing operations, varying from a few months up to 1 year, and mostly depending to the persistence of riverbed alteration, to seasons, and to site specificities such as the provision of macroinvertebrates by undisturbed tributaries (Espa et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, Heptageniidae, Perlodidae and Nemouridae did not recover or displayed the longest recovery times within the monitored year. Several studies (e.g., Doretto et al, 2019;Kaller & Hartman, 2004) reported that members of EPT group, such as the families just mentioned, are particularly sensitive to sedimentation.…”
Section: Discussionmentioning
confidence: 98%